Audit Methodology in Facing Financial Risk: Perspectives from Internal Auditors - Wijaya, Erwin; Pratiwi, Gina; Surya, Dino; Permata, Hanna; Wulandari, Jihan (Golden Ratio of Auditing Research, 2021)
This study investigates the role of audit methodology in addressing financial risks from the perspectives of internal auditors. The research aims to understand the importance of risk assessment, challenges in implementing audit methodology, effectiveness of audit methodology in mitigating financial risks, and recommendations for enhancing audit methodology. Thematic analysis was employed to analyze interviews with internal auditors, revealing key themes and patterns. The findings highlight the critical role of risk assessment in audit methodology, emphasizing its significance in guiding audit planning and resource allocation. Internal auditors identified challenges such as the dynamic nature of financial risks, technological advancements, regulatory requirements, and resource constraints. Despite these challenges, auditors expressed varying levels of confidence in the effectiveness of audit methodologies, with some acknowledging limitations and areas for improvement. Recommendations for enhancing audit methodology include investing in training and development programs, leveraging technology, enhancing communication and collaboration, and fostering a culture of innovation. The study contributes to the literature by providing insights into the challenges and opportunities associated with audit methodology in mitigating financial risks, emphasizing the need for continuous adaptation and innovation. The implications extend to both theoretical and managerial domains, offering practical guidance for strengthening internal audit functions and enhancing organizational resilience against financial risks.